Characterization of field pea (Pisum sativum) resistance against Peyronellaea pinodes and Didymella pinodella that cause ascochyta blight - Joshi, Sameer; Pandey, Babu Ram; Rosewarne, Garry (Frontiers in Plant Science, 2022)
Ascochyta blight is one of the most destructive diseases in field pea and is caused by either individual or combined infections by the necrotrophic pathogens Peyronellaea pinodes, Didymella pinodella, Ascochyta pisi and Ascochyta koolunga. Knowledge of disease epidemiology will help in understanding the resistance mechanisms, which, in turn, is beneficial in breeding for disease resistance. A pool of breeding lines and cultivars were inoculated with P. pinodes and D. pinodella to study the resistance responses and to characterize the underlying resistance reactions. In general, phenotypic analysis of controlled environment disease assays showed clear differential responses among genotypes against the two pathogens. The released variety PBA Wharton and the breeding line 11HP302-12HO-1 showed high levels of resistance against both pathogens whereas PBA Twilight and 10HP249-11HO-7 showed differential responses between the two pathogens, showing higher resistance against D. pinodella as compared to P. pinodes. OZP1604 had high infection levels against both pathogens. Histochemical analysis of leaves using diamino benzidine (DAB) showed the more resistant genotypes had lower accumulation of hydrogen peroxide compared to susceptible genotypes. The digital images of DAB staining were analyzed using ImageJ, an image analysis software. The image analysis results showed that quantification of leaf disease infection through image analysis is a useful tool in estimating the level of cell death in biotic stress studies. The qRT-PCR analysis of defense related genes showed that partially resistant genotypes had significantly higher expression of PsOXII and Pshmm6 in the P. pinodes treated plants, whereas expression of PsOXII, PsAPX1, PsCHS3 and PsOPR1 increased in partially resistant plants inoculated with D. pinodella. The differential timing and intensity of expression of a range of genes between resistant lines challenged with the same pathogen, or challenged with different pathogens, suggests that there are multiple pathways that restrict infection in this complex pathogen-host interaction. The combination of phenotypic, histochemical and molecular approaches provide a comprehensive picture of the infection process and resistance mechanism of pea plants against these pathogens.